2018
DOI: 10.1371/journal.pone.0194440
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pharmacologic sclerostin inhibition or testosterone administration on soleus muscle atrophy in rodents after spinal cord injury

Abstract: Sclerostin is a circulating osteocyte-derived glycoprotein that negatively regulates Wnt-signaling after binding the LRP5/LRP6 co-receptors. Pharmacologic sclerostin inhibition produces bone anabolic effects after spinal cord injury (SCI), however, the effects of sclerostin-antibody (Scl-Ab) on muscle morphology remain unknown. In comparison, androgen administration produces bone antiresorptive effects after SCI and some, but not all, studies have reported that testosterone treatment ameliorates skeletal muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 44 publications
3
30
0
Order By: Relevance
“…Our laboratory has developed a rodent severe contusion SCI model, that displays several characteristics of the severe incomplete SCI population, including the complete inability to support the hindlimbs in stance or to perform voluntary over‐ground stepping for at least 3 months postinjury, extensive cancellous bone deficits at the distal femur and proximal tibia (Otzel, Conover, et al, ), and ~50% lower circulating testosterone than uninjured controls for upwards of 2 months postinjury (Beggs et al, ; Otzel, Conover, et al, ; Yarrow, Conover, et al, ). Using this model, we have reported a >50% reduction in soleus muscle fiber cross‐sectional area (fCSA) occurs within 21 days of SCI, although we did not observe definitive signs of the hallmark slow‐oxidative to fast‐glycolytic fiber‐type transition at this relatively early postinjury time point (Phillips et al, ). Furthermore, we have reported that testosterone enanthate (TE) drug treatment attenuated cancellous bone loss and maintained mass of the sublesional androgen‐sensitive non–weight‐bearing levator ani/bulbocavernosus (LABC) muscle complex in both young (Yarrow, Conover, et al, ) and skeletally mature rodents after severe SCI (Phillips et al, ; Yarrow et al, ), with supraphysiologic TE producing the most robust effects.…”
Section: Introductionmentioning
confidence: 61%
See 4 more Smart Citations
“…Our laboratory has developed a rodent severe contusion SCI model, that displays several characteristics of the severe incomplete SCI population, including the complete inability to support the hindlimbs in stance or to perform voluntary over‐ground stepping for at least 3 months postinjury, extensive cancellous bone deficits at the distal femur and proximal tibia (Otzel, Conover, et al, ), and ~50% lower circulating testosterone than uninjured controls for upwards of 2 months postinjury (Beggs et al, ; Otzel, Conover, et al, ; Yarrow, Conover, et al, ). Using this model, we have reported a >50% reduction in soleus muscle fiber cross‐sectional area (fCSA) occurs within 21 days of SCI, although we did not observe definitive signs of the hallmark slow‐oxidative to fast‐glycolytic fiber‐type transition at this relatively early postinjury time point (Phillips et al, ). Furthermore, we have reported that testosterone enanthate (TE) drug treatment attenuated cancellous bone loss and maintained mass of the sublesional androgen‐sensitive non–weight‐bearing levator ani/bulbocavernosus (LABC) muscle complex in both young (Yarrow, Conover, et al, ) and skeletally mature rodents after severe SCI (Phillips et al, ; Yarrow et al, ), with supraphysiologic TE producing the most robust effects.…”
Section: Introductionmentioning
confidence: 61%
“…Using this model, we have reported a >50% reduction in soleus muscle fiber cross‐sectional area (fCSA) occurs within 21 days of SCI, although we did not observe definitive signs of the hallmark slow‐oxidative to fast‐glycolytic fiber‐type transition at this relatively early postinjury time point (Phillips et al, ). Furthermore, we have reported that testosterone enanthate (TE) drug treatment attenuated cancellous bone loss and maintained mass of the sublesional androgen‐sensitive non–weight‐bearing levator ani/bulbocavernosus (LABC) muscle complex in both young (Yarrow, Conover, et al, ) and skeletally mature rodents after severe SCI (Phillips et al, ; Yarrow et al, ), with supraphysiologic TE producing the most robust effects. However, in our previous studies, supraphysiologic TE did not prevent the soleus fCSA atrophy after severe SCI, perhaps because the soleus exhibits ~70% lower androgen receptor expression than the androgen‐sensitive LABC (Phillips et al, ) or because the TE treatment duration (21 days) was not sufficient to observe muscular improvements.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations